2011
DOI: 10.1260/0144-5987.29.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Coal Structures: FTIR Analyses of Experimental Simulations and Naturally Matured Coals in the Ordos Basin, China

Abstract: A series of coals of varying rank, from brown coal to anthracite, were studied by Fourier transform infrared spectroscopy (FTIR). Curve-fitting analysis was employed to characterize coal structural evolution during the coalification process. The study was carried out on samples of a natural evolutionary series as well as experimental simulation coals dispersed on KBr pellets throughout the Ordos Basin, China. The results showed that the infrared spectrum of coal allowed quality and even quantity identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 44 publications
(67 reference statements)
0
28
0
Order By: Relevance
“…28) In the current experiments, more focus was put on aromatic CH (3 030-2 950 cm − 1 ) and aliphatic CH (2 920-2 850 cm − 1 ) and the peak areas were evaluated by integration because those functional groups are known to be closely related to the mean reflectance and coal fluidity affecting critical quality of coals. [21][22][23] As shown in Fig. 3, A aroCH /A aliCH shows a close relationship with the mean reflectance which is one of the factors affecting coal rank.…”
Section: Correlation Between Ft-ir Spectra and Coalmentioning
confidence: 66%
See 1 more Smart Citation
“…28) In the current experiments, more focus was put on aromatic CH (3 030-2 950 cm − 1 ) and aliphatic CH (2 920-2 850 cm − 1 ) and the peak areas were evaluated by integration because those functional groups are known to be closely related to the mean reflectance and coal fluidity affecting critical quality of coals. [21][22][23] As shown in Fig. 3, A aroCH /A aliCH shows a close relationship with the mean reflectance which is one of the factors affecting coal rank.…”
Section: Correlation Between Ft-ir Spectra and Coalmentioning
confidence: 66%
“…Several studies already reported that the ratio of peak areas of aromatic CH and aliphatic CH in raw coals is closely related to coal properties such as reflectance and fluidity. [21][22][23] However, the spectral analyses of real time change have rarely been carried out although some of the previous studies dealt with coal spectra of raw coals. Most of FT-IR researches were carried out to measure the spectra at each temperature by using the different pellets of individual coal.…”
Section: Introductionmentioning
confidence: 99%
“…According to the oxygen consumption and index gases analysis of coal, the oxidation activity of BO coal is weakest and that of BA coal strongest. 4 ]. The FTIR spectra results demonstrate that ILs treatment can break and dissolve some active structures in coal, such as associated hydrogen bonds and methylene, at room temperature and inhibit the low-temperature oxidation activity of coal, where the inhibition effect of [BMIm][OTf] is the strongest.…”
Section: Oxygen Consumption and Index Gases Analysis During Low-tempementioning
confidence: 99%
“…Research on coal spontaneous combustion supports the viewpoint that some active structures in coal can react with oxygen at low temperatures, which can result in self-heating of coal and, in extreme cases, spontaneous combustion of coal [1,2]. These structures are mainly the aliphatic hydrocarbon groups and oxygen functional groups [3][4][5]. Therefore, coal spontaneous combustion can be prevented effectively by inhibiting low-temperature oxidation of these active structures in coal.…”
Section: Introductionmentioning
confidence: 99%
“…Previous works have indicated that coal rank is a dominating control on methane capacity, And both microporosity and sorption capacity of CBM increase with increasing coal rank (Clarkson and Bustin, 1996;Prinz and Littke, 2005;Sun et al, 2005Sun et al, , 2010Yao et al, 2011). Based on sufficient statistics, a relational model between rank and methane capacity is constructed (Su et al, 2005).…”
Section: Influence Of Coal Rankmentioning
confidence: 99%